Spatiotemporal Water Quality Assessment of Dumate Al-Jandal Lake (KSA) Using Environmetric Techniques - Al-Sheraideh, Mohammed Sharif (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2018)
Environmentally, the objective of the study conducted in evaluating the spatiotemporal water quality asessment using some statistical techniques. Physicochemical characteristics determination applied on Dumate al-Jandal Lake, whether the analysis of water quality is good for agricultural irrigation or other ecosystem services. Sampling and measurements were taken weekly at five sites started from February 2009 to January 2011. Descriptive analysis as well as the 95% confidence intervals, Wilks’ Lambda Statistics, MANOVA and ANOVA showed no presence of significant difference at the level of p < 0.05 among seasons and between sites, except the mean effect only for some parameter like Iron on the physiochemical parameters whereas a significant difference among the mean of physiochemical characteristics of water data to sites for the parameters like pH and nitrate, while there are no differences among the mean of physiochemical characteristics of water data of sites for the other parameters. Multiple comparison t-test shows the differences between means Sites of (1, 3) and (2, 5) as well as between (3) and (5) for the parameter pH. Results showed a significant difference at (p < 0.05) between the means of Site (1) and all Sites (3, 4 and 5) as well as between Site (2) and (3) for nitrate, but a significant difference at (p < 0.05) among the mean associated with seasons for temperature, electrical conductivity, specific density, sulphate, nitrite, ammonia, chloride, total hardness, total alkalinity, manganese, magnesium and calcium hardness, while there are no differences among the mean of seasons for the other parameters. Whereas results of multiple comparison t-test showed that a differences between the means of season (i) and season (j), for each parameter. The study concluded that some of physicochemical parameters were reflected the presence of pollutants and absence of good ecosystem activities. To avoid seasonal pollution, water lake management are recommended.